HASHEM É O MEU PASTOR: A CONSTRUÇÃO SEMIÓTICA DA CONFIANÇA NOS SALMOS - THAÍSSA SOARES SILVA (2024)
Considering the importance of the Holy Scriptures for countless cultures, they have become a focus of research across various interpretative perspectives; in this context, the present work investigates how trust is constituted as a semiotic passion in the Book of Psalms. This passion emerges as a central element in the relationship between the psalmist and God, revealed through figures and themes that construct isotopies, such as divine protection, salvation, and praise, highlighting the depth of the psalmist's faith and dependence on the divine. The analysis is anchored in concepts from discursive semiotics. Specific textual passages revealing the psalmist's trust in God were chosen for analysis, including Psalms 23, 27, 40, 63, 71, and 121. Importantly, the analysis considers two languages: primarily Portuguese, the language in which the dissertation is developed, and Hebrew as an analytical support, the original language of these texts. The analysis covers not only linguistic meanings but also the cultural nuances and sense effects present in both languages, using both the Hebrew and Portuguese versions from the book Tehilim Keter David (2020). The transliteration used for the Psalms texts is found in O livro dos salmos com transliteração linear, the 2017 version, which contains the texts in Hebrew, in Portuguese (interlinear), and transliterated. It is worth noting that this work is constructed by selecting figurative elements in Hebrew and examining how they build the present isotopies. For this, the research utilized Bertrand's (2003) concept, understanding that comprehending a meaning involves not only identifying objects in the world but also recognizing the relationships among them, which construct meanings. These isotopies are comprehensible through the figurative and thematic elements that compose the poetic texts in the Psalms. Regarding isotopies, we must also note that we consider the analysis of trust, bearing in mind that, in Hebrew, the relationship between אמונה Emunah, transliterated, superficially translated as faith, and the lexeme ביטחון Bitachon, transliterated, which represents full trust in God, reveals the connection between these concepts. This underscores the importance of analyzing the lexemes and their meaning constructions in Hebrew, since the texts were originally written in that language, allowing for a deeper understanding of the cultural meanings and sense effects associated with them. Furthermore, we recognize that the texts selected for analysis form a cohesive set of meanings, intrinsically related to the Hebrew language.